If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(-3k + 4) + -5 = 145 Reorder the terms: 6(4 + -3k) + -5 = 145 (4 * 6 + -3k * 6) + -5 = 145 (24 + -18k) + -5 = 145 Reorder the terms: 24 + -5 + -18k = 145 Combine like terms: 24 + -5 = 19 19 + -18k = 145 Solving 19 + -18k = 145 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-19' to each side of the equation. 19 + -19 + -18k = 145 + -19 Combine like terms: 19 + -19 = 0 0 + -18k = 145 + -19 -18k = 145 + -19 Combine like terms: 145 + -19 = 126 -18k = 126 Divide each side by '-18'. k = -7 Simplifying k = -7
| 5(-1.26666)+5y=9 | | 154-4x=6x+19 | | 7+9x=10x | | 52-3u=8 | | -174=6(-4r+3) | | a^2+11a=-1 | | 0.333333333x=18 | | -36-2=13-9x | | w(w+2)=168 | | -2x+y=-19 | | 7(1+7x)=350 | | 0.2x=6 | | 4g^2-3g-2=0 | | 0.25x=-12 | | -m^2+m-2=-2m^2 | | 2xz=4x+6yx | | 4c^2-15c-25=0 | | 7x=100 | | k^2+10k+21=0 | | 3(40+20)=40x | | m^2+5m=3 | | 7(1-4m)=-147 | | 3(x+1)-4=1-x | | x=200 | | 5(2x+1)=12 | | -35=7x | | 7n-2=-51 | | 6x-5=7x | | -12-9x=-8x | | -9=z+40 | | 5y^2-5y-30= | | 20-6x=-5x |